Adab Menuntut Ilmu Dalam Hadis: Tantangan Teknologi Modern - Andi Iting; La Ode Ismail Ahmad; Abdul Rahman Sakka (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2025)
This study examines the etiquette of seeking knowledge from the perspective of the hadith of the Prophet Muhammad SAW as a foundation for learning ethics relevant to the challenges of education in the modern technological era. The development of digital technology has changed the way humans acquire and produce knowledge, but these changes are often not accompanied by the strengthening of ethical values in the learning process. The research gap arises from the lack of studies that systematically integrate the principles of etiquette of seeking knowledge based on hadith with the context of contemporary technology-based learning. This study aims to identify the principles of etiquette of seeking knowledge in hadith and analyze their relevance to modern educational practices. The research approach uses a qualitative method with a library study design through thematic hadith analysis and a review of international educational literature. The results show that etiquette of seeking knowledge in hadith includes righteous intentions, humility, respect for teachers, patience in the learning process, and moral responsibility in the use of knowledge. These findings confirm that the value of etiquette has conceptual significance in building ethical and character-based digital learning. The implications of this study provide theoretical contributions to the development of Islamic education studies and serve as a conceptual basis for the formulation of values-based educational strategies in the technological era.